Study of Seed Germination and Agro-technique of Asparagus racemosus Willd. in Mid Hills of Western Himalaya - Gopichand,; Singh, R. D.; Meena, R. L. (Indian Forester, 2013)
Asparagus racemosus is a medicinally important plant, distributed in Himalayan and sub-Himalayan region of India. The root is used in many herbal preparations. Effect of some growth hormones and chemicals was studied on its seed germination. Concentrations of IAA (Indole-acetic acid) 100, 200 and 500 mg/l, IBA (Indole-butric acid), NAA (naphthalene acetic acid), Salicylic acid, Tanic acid with water soaking as control were used. Seed germination was st started on 21st day of seed sowing in IBA treated seeds. Highest seed germination 89.33% and 85% were recorded in IBA, 500 and 200 mg/l, respectively. Lowest seed germination was recorded in Tanic acid 100 mg/l 50.33% and in control 43%. The maximum shoot length of 18.37 cm, 18.47 cm and 18.70 cm were recorded respectively in IBA 200, 500 mg/l and NAA 500 mg/l. While root length 6.40 cm and 6.83 cm was recorded in IBA 200 and 500 mg/l after 30 days of seed germination. A field trial was also laid out for standardization of propagation techniques by using different FYM applications. Significantly highest fresh biomass of rhizomes 132.50 t/ha and dry biomass 15.90 t/ha was recorded with the dose of FYM 30 t/ha and minimum 8.33 t/ha in FYM 0 t/ha. Various growth parameters were also recorded in the field experiment.